A Mobile Application of Equipment Maintenance Plan for a Refinery Plant - Masrullah, Masfufah (IRC, 2019)
As every sector is going to implement Industry Revolution 4.0, any innovation regarding technology is very interesting in the eyes of every company of every sector. The old way of doing things need to be change as it may not be relevant to be implemented today and to be parallel to the rapid advancement of technology, every innovation is important. Innovation may be look as bad since it will be replacing some things, some processes, or maybe some people. As for any sector, to ensure that the production is meeting the expectation. The excellent operation is very important and to ensure operation is operating well, equipment maintenance is important. This to ensure that the equipment is on its optimum condition. The unnecessary problem face during the process of maintaining equipment need to be avoided as it will lead to waste of time. As time is very priceless, we cannot afford to waste it for unnecessary problem that can be avoided with the implementation of Mobile Application Maintenance Plan. This project that is inspired based on the problem face during maintenance plan data retrieval process in Malaysian Refining Company Sdn Bhd (MRCSB). An interview is conducted at MRCSB to know more about the maintenance plan and to get the overview of the system they are using right now and how the Mobile Application Maintenance Plan would help in their field. The result and recommendations are shared at the end of project for future enhancement.